The Learning Process Of Children With Special Needs At Salsabila Inclusive School, Purwakarta - Imam Tabroni; Solihah Bagus; Sanusi Uwes; Manpam Drajad; Ijah Bahijah (Program Studi Pendidikan Agama Islam (PAI) Sekolah Tinggi Agama Islam Al Azhar, 2022)
The purpose of this study was to find out the learning process of children with special needs at the Salsabila Elementary School in Purwakarta. Children with special needs often do not get the same learning rights as other normal children. Therefore, it is necessary to study and find the right solution regarding this problem at Salsabila Elementary School. The research method uses an ethnographic design with a qualitative approach. data collection techniques through in-depth observation, interviews, and documenting the data. Data analysis by triangulation and interpretation. The results showed that the learning of children with special needs with other normal children in Salsabila Purwakarta Elementary School showed no difference. All children have the same right to learn with the educators, methods, media, and curriculum applied in the school. Learning prioritizes character building or soft skills compared to cognitive emphasis.